SUBTITLED VIDEO OF PROCEDURE TEXT: MEDIA FOR TEACHING LISTENING TO ELEMENTARY STUDENTS - Putri Novitasari (EZRA SCIENCE BULLETIN, 2024)
This research motivated by the goal to achieve a listening improvement of elementary school students. The purpose of this research was to determine the improvement of listening skill of fifth-grade elementary school students by using subtitled video. Students are hoped to be able to reach their maximal achievement in score after doing it. The object of this research consisted of 34 students of elementary school. This research used experimental model with one group of pre-test and post-test design. The result of this research was subtitled video had significant influence for students’ listening skill in making a recipe. It is proven by increased score of students after taught using short animation subtitle. The data showed that the mean of students in pre-test was 56.62 and the mean score of post-test was 77. 94. Students felt enjoy and happy by listening subtitled video. They were not only studied the expression but also viewed the visualization of giving direction. That was enjoyable for them.